THERMAL CONDUCTIVITY OF MATERIALS: IMPLICATIONS FOR HEAT MANAGEMENT IN MEDICAL DEVICES - Jaiswal, Shweta; Jaiswal, Ayush (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Effective heat management is crucial for the optimal performance and safety of medical devices. This paper explores the role of thermal conductivity in material selection for medical devices, emphasizing its impact on heat dissipation and device reliability. Various materials, including metals, ceramics, and polymers, are analysed to understand their thermal properties and implications for device design. Metals such as copper and aluminium exhibit high thermal conductivity, making them suitable for high-heat applications, while polymers like polycarbonate offer lower thermal conductivity, beneficial for insulation purposes. Experimental methods for measuring thermal conductivity, including the laser flash method, and guarded hot plate method, are discussed to provide accurate data essential for material selection. The paper also addresses common heat management challenges in medical devices, including overheating in implants and imaging systems, and proposes solutions such as advanced cooling systems and material innovations. The findings highlight the importance of aligning material properties with specific device requirements to enhance performance and patient safety. Future research directions include investigating long-term effects of thermal cycling and exploring new materials and cooling technologies.